Freedom from the Source Text: Teaching Trilby and Its Adaptation Network. - Harrison, Bill (CEA Critic, 2025)
As conventional adaptation pedagogy often focuses on specific canonical works, uses ahistorical, one-to-one text-to-film comparisons, and downplays the complexity of adaptive processes, this essay will explore teaching what Kate Newell terms the "adaptation network" as an alternative. Using George Du Maurier's 1894 novel Trilby and its extensive series of adaptations as a case study, I shall examine a web of interconnected works across various media and decades. This kind of model encourages deeper critical analysis of how cultural meaning evolves, revealing adaptation as a complex, historically situated process rather than a simple, comparative transcoding.